Predictors of lower health-related quality of life after operative repair of diaphyseal femur fractures in a low-resource setting. Issue 7 (July 2018) - Ibrahim, John M.; Conway, Devin; Haonga, Billy T.; Eliezer, Edmund N.; Morshed, Saam; Shearer, David W.
Abstract: Background: Little data exists on the negative impact of orthopaedic trauma on quality of life (QOL) in low- and middle-income countries (LMICs). The goal of this study is to investigate the factors associated with lower QOL after operative fixation of femoral shaft fractures in adult patients in a low-resource setting. Methods: This prospective cohort study followed 272 factures in adults undergoing operative fixation for diaphyseal femur fractures at Tanzania. Patient demographics, injury characteristics, treatment modalities, and functional outcomes up to 1-year post-operatively were evaluated for association with 1-year post-operative EQ-5D QOL scores via univariate linear regression analysis. Results: EQ-5D values were significantly lower at 1 year than at baseline (0.941 vs 0.991, p < 0.0005). Conclusions: Operative fixation of femoral shaft fractures in LMICs results in return to near baseline QOL. Demographic and treatment factors were not significantly associated with EQ-5D. and several markers of recovery were associated with lower 1 year QOL, including pain, knee stiffness, delayed radiographic healing, complications requiring reoperation. Efforts to reduce perioperative complications may help improve post-operative QOL.